Transcatheter Aortic Valve Implantation: The Evolving Role of the Radiologist in 2021 - Salgado, Rodrigo; El Addouli, Haroun; Budde, Ricardo P J (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Background Transcatheter aortic valve implantation (TAVI) has gained worldwide acceptance and implementation as an alternative therapeutic option in patients with severe aortic valve stenosis unable to safely undergo surgical aortic valve replacement. This transformative technique places the radiologist in a key position in the pre-procedural assessment of potential candidates for this technique, delivering key anatomical information necessary for patient eligibility and procedural safety. Recent trials also provide encouraging results to potentially extend the indication to patients with safer risk profiles.Method The review is based on a PubMed literature search using the search terms “transcatheter heart valve”, “TAVI”, “TAVR”, “CT”, “imaging”, “MR” over a period from 2010–2020, combined with personal comments based on the author’s experience.Results and Conclusion CT plays a prominent role in the pre-procedural workup, delivering as a true 3D imaging modality optimal visualization of the complex anatomy of the aortic root with simultaneous evaluation of the patency of the different access routes. As such, the contribution of CT is key for the determination of patient eligibility and procedural safety. This input is supplementary to the contributions of other imaging modalities and forms an important element in the discussions of the Heart Valve Team. Knowledge of the procedure and its characteristics is necessary in order to provide a comprehensive and complete report. While the role of CT in the pre-procedural evaluation is well established, the contribution of CT and MR and the clinical significance of their findings in the routine follow-up after the intervention are less clear and currently the subject of intense investigation. Important issues remain, including the occurrence and significance of subclinical leaflet thrombosis, prosthetic heart valve endocarditis, and long-term structural valve degeneration.Key Points: Citation Format
Keywords: TAVI; aortic valve; aortic valve stenosis; TAVR; CT angiography